2000
DOI: 10.1046/j.1468-3148.2000.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cost‐Effectiveness of Supported Employment for People with Severe Intellectual Disabilities and High Support Needs: a Pilot Study

Abstract: The costs and outcomes of supporting seven people with severe intellectual disabilities and high support needs in part‐time employment were compared with those of a Special Needs Unit (SNU) of a day centre, both within‐subject and against an equal‐sized comparison group. The income of those employed was described. Direct observation of the employment activities and representative SNU activities were undertaken to assess participant engagement in activity and receipt of assistance, social contact in general and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
0
8
0
4
Order By: Relevance
“…Los análisis coste-beneficio proporcionan información sobre los costes de los servicios en relación a los beneficios que de éstos se derivan, para poder así tomar decisiones al comparar entre dos opciones de servicios para un objetivo similar (Beyer y Kilsby, 1998;Cimera, 2006aCimera, , 2007aCimera, , 2007bNarrillos, 2010;Shearn et al, 2000). Estos análisis son, por tanto, utilizados para aportar datos monetarios y permitirnos conocer qué opción es la más rentable, es decir, supone un mayor beneficio en relación al gasto realizado (Beyer y Kilsby, 1998;Cimera, 2010Cimera, , 2007aCimera, , 2007bShearn et al, 2000), siendo importante que ambas opciones sean equivalentes, o la comparación perdería la utilidad (Cimera, 2007a(Cimera, , 2007b. El problema de estos análisis es la mutabilidad, ya que en el momento que cambie una de las variables contempladas (subvenciones, aumentos salariales, cambio del valor monetario, etc.…”
Section: Análisis Coste-beneficio En Empleo Con Apoyo Y Protegidounclassified
See 3 more Smart Citations
“…Los análisis coste-beneficio proporcionan información sobre los costes de los servicios en relación a los beneficios que de éstos se derivan, para poder así tomar decisiones al comparar entre dos opciones de servicios para un objetivo similar (Beyer y Kilsby, 1998;Cimera, 2006aCimera, , 2007aCimera, , 2007bNarrillos, 2010;Shearn et al, 2000). Estos análisis son, por tanto, utilizados para aportar datos monetarios y permitirnos conocer qué opción es la más rentable, es decir, supone un mayor beneficio en relación al gasto realizado (Beyer y Kilsby, 1998;Cimera, 2010Cimera, , 2007aCimera, , 2007bShearn et al, 2000), siendo importante que ambas opciones sean equivalentes, o la comparación perdería la utilidad (Cimera, 2007a(Cimera, , 2007b. El problema de estos análisis es la mutabilidad, ya que en el momento que cambie una de las variables contempladas (subvenciones, aumentos salariales, cambio del valor monetario, etc.…”
Section: Análisis Coste-beneficio En Empleo Con Apoyo Y Protegidounclassified
“…Podemos encontrar evidencias de resultados (Beyer, 2012;Beyer et al, 1999;Cimera, 2012bCimera, , 2011aCimera, , 2011bCimera, , 2010Cimera, , 2009aCimera, , 2008Cimera, , 2007aCimera, , 2006aCimera y Burgess, 2011;Shearn et al, 2000) sobre los beneficios del ECA y sus mejores resultados respecto al empleo protegido desde las tres perspectivas de análisis citadas: persona, empresa y sociedad.…”
Section: Análisis Coste-beneficio En Empleo Con Apoyo Y Protegidounclassified
See 2 more Smart Citations
“…21 shown that supported employment is cost efficient (as well as cost effective when compared with sheltered workshops) for individuals with all types of disabilities, including individuals with severe disabilities. [21][22][23][24][25][26][27][28] Further, the cost efficiency of supported employment programs increases with each year of program operation, with the benefits of supported employment exceeding the costs by the fourth year of operation. 21 Information regarding the long-term costs of supported employment services as well as the long-term benefits to consumers is crucial in determining the efficacy of supported employment in individuals with TBI.…”
mentioning
confidence: 99%